RANCANG BANGUN PROTOTIPE SISTEM HYBRID PV-PLN-BATERAI PADA KINCIR AIR DI TAMBAK UDANG - Rachmad Ikhsan; Zoel Fachri (J-Innovation, 2021)
The source of electrical energy to turn on the waterwheel drive in the majority of shrimp ponds is currently still sourced from PLN and backup energy comes from generators. Fossils will continue to decrease and take a long time to be renewed, so to overcome this, a waterwheel is designed with a source of electricity generation from renewable energy in the form of energy from the sun (photovoltaic) combined with electrical energy from PLN and batteries as backup energy . The method of switching electrical energy through the settings of the Arduino controller with input from the input voltage sensor (ZMPT 101B). From the test results of the PV-PLN-Battery hybrid system, the switching process can work well and from the results of the solar panel test it can be seen that there is no significant difference taken with a time difference of 1 (one) hour where when the weather is sunny and cloudy the voltage is higher. The resulting solar panels look stable.